Transforming Civic Education through Reflection on Human Rights Violations in South Africa (JED (Jurnal Etika Demokrasi), 2026)
The urgency of this research arises from the persistent need to strengthen human rights awareness, democratic responsibility, and ethical citizenship within Civic Education, particularly in societies that continue to face the legacy of historical injustice and social fragmentation. This study aims to examine South Africa’s post-apartheid experience, especially its response to systemic human rights violations, and to identify its relevance for transforming Civic Education in Indonesia. This research employed a qualitative method through a structured literature review using a structural approach. Data were collected from scholarly books, peer-reviewed journal articles, legal documents, and relevant human rights reports, then analyzed thematically to identify conceptual relationships among apartheid, reconciliation, Ubuntu, human rights education, and Indonesian Civic Education. The findings show that South Africa transformed the legacy of institutionalized racial discrimination into an educational resource through the Truth and Reconciliation Commission and the integration of Ubuntu values into civic and moral learning. These mechanisms promoted truth-telling, historical reflection, empathy, restorative justice, and participatory citizenship. The findings also indicate that Indonesian Civic Education remains largely normative and legalistic, requiring deeper integration of historical consciousness, human rights reflection, and dialogical pedagogy. This study concludes that Civic Education in Indonesia should shift toward a more critical, participatory, ethical, and humanistic model. The novelty of this research lies in its conceptual synthesis of South Africa’s reconciliation-based civic learning with Indonesia’s Pancasila-based educational framework. This research contributes to the development of comparative Civic Education by offering a reflective model for integrating human rights, moral reasoning, and democratic citizenship into Indonesian educational practice.